A randomized controlled trial of the effect of supervised exercise on functional outcomes in older African American and non‐Hispanic White breast cancer survivors: Are there racial differences in the effects of exercise on functional outcomes?. Issue 12 (15th March 2022) - Owusu, Cynthia; Margevicius, Seunghee; Nock, Nora L.; Austin, Kristina; Bennet, Elizabeth; Cerne, Stephen; Hergenroeder, Paul; Moore, Halle C. F.; Petkac, Jean; Schluchter, Mark; Schmitz, Kathryn H.; Webb Hooper, Monica; et al.
Abstract : Background: The objective of this study was to test the hypothesis that exercise would be more effective than a support group plus Fitbit (SG+Fitbit) program in improving functional outcomes in older breast cancer survivors (BCSs) and that race would moderate the exercise effect on outcomes. Methods: Older African American (AA) and non‐Hispanic White (NHW) BCSs were purposively recruited and enrolled into the 52‐week randomized controlled trial. The interventions included 20 weeks of supervised moderate‐intensity aerobic and resistance training followed by 32 weeks of unsupervised exercise called IMPROVE (n = 108) and a 20‐week SG+Fitbit program followed by 32 weeks of unsupervised activity (n = 105). Study outcomes were assessed at 20 and 52 weeks. The primary outcome was the change in Short Physical Performance Battery (SPPB) scores 20 weeks from the baseline between arms. Secondary outcomes included change in the 6‐Minute Walk Test (6MWT) in meters 20 weeks from the baseline between arms. General linear regression and multivariable logistic regression analyses were used. Results: The mean age was 71.9 years (SD, 5.9 years), and 44% were AA. SPPB scores did not differ between arms (adjusted difference in mean change, 0.13; 95% CI, –0.28 to 0.55; P = .53). However, the exercise arm (vs the SG+Fitbit arm) improved on the 6MWT (21.6 m; 95% CI, 2.5‐40.6 m; P = .03). Race moderated the exercise effect on the 6MWT (adjusted interaction effect, 43.3 m; 95% CI, 6.3‐80.2 m; P = .02); this implied that the change in the adjusted mean for the 6MWT at 20 weeks from the baseline was 43.3 m higher in AA exercise participants versus NHW exercise participants. Conclusions: Combined aerobic and resistance exercise appears to improve physical performance in older BCSs, and the exercise effect might be moderated by race, with AAs appearing to derive larger benefits in comparison with NHWs. Larger studies are warranted to confirm the study findings. Abstract : Combined aerobic and resistance exercise appears to improve functional outcomes in older African American and non‐Hispanic White breast cancer survivors. The exercise effect might be moderated by race.